SECURITY CHALLENGES OF THE NEW AMERICAN ADMINISTRATION (Annual of the Faculty of Philosophy in Skopje, 2010)
The arrival of a new U.S. president, Barack Obama marks the beginning of a new era in international relations. The period of Uni-polarization, characteristic for the years after the Cold War slowly decrease his intensity and his place multi-polarization yields. In the context of such global changes, the new U.S. administration made attempts to revise their positions by preventing timely security challenges. This paper provides a critical review of the position of the new U.S. administration of the European continent, relations with European partners and the spread of NATO eastward. Also, review of relations with Russia and a new impulse to "reset" of relations with the largest Eurasian geopolitical actor. However it seems that the biggest security challenges for the United States mostly are manifesting in the area of the Middle East, i.e. Iraq, Iran, Afghanistan, Pakistan, and North Korea.
Keywords: GEOPOLITIC; GEOSTRATEGY; SECURITY; SECURITY CHALLENGES; OBAMA